Lady Eastlake and the Characteristics of the Old Masters - Julie Sheldon (19, 2019)
Lady Eastlake was one of a number of experts and commentators to lay out the ways with which readers could engage with works by the old masters. This article considers the modes in which she presented her expertise and the manner in which she laid out her special form of commentary. Looking particularly at her Five Great Painters of 1883, the article examines Eastlake’s discussion of character in old master painting, presenting her evaluations of specific old masters in relation to some of the broader critical and analytical concerns at work in Victorian letters.